2021
DOI: 10.1007/s11562-021-00473-3
|View full text |Cite
|
Sign up to set email alerts
|

Muslim typologies in Australia: Findings of a national survey

Abstract: Numerous researchers in the field of Islamic and Muslim Studies have proposed various typologies to categorize Muslims in relation to their understanding of and identification with Islam. However, to date few studies have conducted the necessary empirical work to determine the numbers of Muslims that identify with the typologies that have been constructed. This article is the first to present findings based on a comprehensive study of Muslims in relation to a spectrum of discursive typologies. The authors cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The authors found that amongst their participants, "75% of religious Muslims appear to support politically moderate Islam, while 25% show support for politically radical Islam" (Achilov and Sen, 2017, 618). While it is beyond the scope of this paper to provide an in-depth overview of existing typologies, further discussion of these conceptual frameworks and their influence of the present study can be found elsewhere (Rane and Duderija, 2021).…”
Section: Converts and Political Islammentioning
confidence: 99%
“…The authors found that amongst their participants, "75% of religious Muslims appear to support politically moderate Islam, while 25% show support for politically radical Islam" (Achilov and Sen, 2017, 618). While it is beyond the scope of this paper to provide an in-depth overview of existing typologies, further discussion of these conceptual frameworks and their influence of the present study can be found elsewhere (Rane and Duderija, 2021).…”
Section: Converts and Political Islammentioning
confidence: 99%
“…Not only in Indonesia, the identity of Islamic traditionalism in India, represented by Sunni group is also confronted by Islamic reformers concerning on the purification of religious teachings [2]. In Australia, the conflict between traditionalist and reformist Islam also occurs despite the limited study of identity [3].…”
Section: Introductionmentioning
confidence: 99%